Near-infrared spectroscopic indices for unresolved stellar populations – II. Index measurements. Issue 4 (24th August 2021) - Gasparri, D; Morelli, L; Ivanov, V D; François, P; Pizzella, A; Coccato, L; Corsini, E M; Dalla Bontà, E; Costantin, L; Cesetti, M
ABSTRACT: We measured the equivalent width of a large set of near-infrared (NIR, 0.8–2.4 μ m) line-strength indices in XShooter medium-resolution spectra of the central regions of 14 galaxies. We found that two aluminum indices, Al at 1.31 μ m and Al1 at 1.67 μ m, and two CO indices, CO1 at 1.56 μ m and CO4 at 1.64 μ m, are tightly correlated with the velocity dispersion. Moreover, the NIR Al and CO1 indices show strong correlations with the optical Mg2 and Mgb indices, which are usually adopted as α /Fe-enhancement diagnostics. The molecular FeH1 index at 1.58 μ m correlates tightly with the optical 〈Fe〉 and [MgFe]′ indices, which are used as total metallicity diagnostics. The NIR Pa β index at 1.28 μ m has a behaviour similar to the optical H β index, which is a diagnostic of mean age. We defined two new composite indices, 〈Al〉 and [AlFeH], as possible candidates to be used as NIR diagnostics of total metallicity and α /Fe enhancement. The NIR 〈Al〉 index has a strong correlation with the optical Mg2 and Mgb indices, while the [AlFeH] index is tightly correlated with the optical 〈Fe〉 and [MgFe]′ indices. The distribution of the data points in the NIR Pa β –〈Al〉 and Pa β –[AlFeH] diagrams mimics that in the optical [MgFe]′–H β and Mgb–〈Fe〉 diagrams, which are widely used to constrain the properties of the unresolved stellar populations. We concluded that some NIR line-strength indices could be useful in studying stellar populations as well as in fine-tuning stellar population models.